FORMATION OF ENVIRONMENTAL COMPETENCE OF FUTURE NURSES IN THE DISCOURSE OF MODERN PROFESSIONAL PEDAGOGY (Innovative professional education, 2024)
The actual problem of the formation of environmental competence of future nurses in professional colleges is highlighted. The essence of the concept of «ecological competence», considered by scientists in the context of the formation of critical thinking, responsibility and the ability not only to identify environmental problems, to find rational ways to solve them, but also to prevent the emergence of the latter, has been clarified.
Keywords: college, environmental competence, future nurses, professional education